Meningkatkan Sanitasi Masyarakat dan Memajukan Umkm di Desa Tegak Kabupaten Klungkung di Masa Pandemi - Ni Ketut Sukiani; Gusti Ayu Made Rai Suarniti (Warmadewa Press, 2021)
This activity aims to improve the level of community hygiene or sanitation and promote Micro, Small and Medium Enterprises (MSMEs) in Tegak Village, Klungkung Regency during the Pandemic Period. This is done by implementing several programs. This activity can be carried out thanks to the collaboration between Warmadewa University and the people of Upright Village. This study was written with a qualitative method, and data collection was carried out by direct observation and interviews. This service activity is carried out by helping promote MSMEs through social media platforms, educating on how to wash hands properly, distributing free masks, and installing educational posters for COVID-19 prevention, as well as assisting with COVID-19 vaccination activities, and assisting after-care activities such as the construction of MCK facilities. and tree planting. The programs that have been implemented well in Tegak Village, Klungkung District, Klungkung Regency include the promotion program for Micro, Small, and Medium Enterprises (MSMEs), an educational program on how to wash hands properly, a program for distributing free masks and the installation of educational posters for COVID-19 prevention, a program to assist in the implementation of COVID-19 vaccination, assisting posyandu activities, handing over direct cash assistance (BLT) for Upright Village funds for the 2021 fiscal year 2021 phase V in May 2021, the village SDGs population data survey program in 2021, and programs to improve sanitation and care for the environment.